GAMBARAN FAAL PARU PADA PASIEN ASMA YANG MELAKUKAN SENAM ASMA DENGAN YANG TIDAK MELAKUKAN SENAM ASMA - Uci Tama Azilla; Sri Melati Munir; Eka Bebasari (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACT Asthma is chronic inflammation disorder of respiratory tract that cause trial episode of symptoms like wheezing, breathlessness, feel heavy in chest, cough especially in the night or early morning that reversible with or without therapy. Spirometry is used in clinical examination to diagnose and evaluation patient with asthma. Asthma gymnastic is one of recommendation exercise therapy to help the process of rehabilitation in asthma patient. This study was cross sectional descriptive that used total sampling method which explained overview lung function of asthma patient that followed asthma gymnastic and not followed asthma gymnastic. In this study, total sampling was 62 patient which 31 asthma patient that followed asthma gymnastic and 31 not followed asthma gymnastic. The result showed asthma patient that followed asthma gymnastic were in the age group 41-50 years old consist of 12 patient (38,7%), most commonly happened in female consist of 24 patient (77,4%), most common not had comorbidities consist of 18 patient (58%), most common patient had family history of asthma consist of 19 patient (61,3%), the lung function was obstructive consist of 17 patient (54.9%), the level of asthma was intermittent consist of 12 patient (38.7%), assessment of asthma control was controlled consist of 14 patient (45.1%) the length of time following the most gymnastic was asthma ≥3 month 19 patient (61,3%). In asthma patient that was not followed asthma gymnastic were in the age group 41-50 years old consist of 13 patient (42%), most commonly happened in female consist of 27 patient (81,7%), most common had comorbidities consist of 18 patient (58%), most common patient not had family history of asthma consist of 16 patient (51,6%), the lung function was restrictive consist of 20 patient (64.5%), the level of asthma was severe persistent consist of 12 patient (38.7%) and assessment of asthma control was controlled consist of 18 patient (58.1%).Keywords: Asthma, asthma gymnastic, spirometry, lung function.